Effects of Methamphetamine Exposure on Lipid Profile and Cardiovascular Risk in Wistar Rats - A. I. Ajayi; I. O. Okoro (Journal of Applied Sciences and Environmental Management, 2024)
Methamphetamine (METH) is a highly addictive psychostimulant that not only impacts the central nervous system but also poses significant risks to metabolic and cardiovascular health. This study investigates the chronic effects of METH on the lipid profile and cardiovascular risk in Wistar rats using appropriate standard method. Data obtained show that methamphetamine induced significant weight loss in the high dose group (from 0.46 to 0.39 g/cm2).  The lipid profile result (table 2) indicated reduction in cholesterol (CHOL), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) levels with higher doses, while triglycerides (TG) increased. The findings revealed that chronic METH intake led to a dose-dependent reduction in body mass index (BMI) and significant alterations in lipid parameters. These suggest that METH alters lipid metabolism, potentially contributing to increased cardiovascular risk in chronic users.